Pan vs. Selective Computed Tomography Scans in Management of Multiple Trauma Patients; a Brief Report - Sabzghabaei, Anita; Shojaee, Majid; Kariman, Hamid; Manouchehrifar, Mohammad; Heydari, Kamran; Sohrabi, Sirus (Archives of Academic Emergency Medicine, 2017)
Introduction: Using pan or selective computed tomography (CT) scan in management of multiple trauma patient is a matter of debate. Therefore, the present study was designed aiming to compare the findings of pan and selective CT scans in management of multiple trauma patients. Method: This is a prospective cross-sectional study, on patients presented to the emergency department (ED) of Shohadaye Haftome Tir Hospital, Tehran, Iran, following blunt multiple trauma over a 1-year period, from March 2014 to March 2015. Findings regarding presence or absence of injury in head, face, neck, chest, abdomen and hip were compared between patients that underwent pan and selective CT using SPSS 21. Results: 443 patients with the mean age of 34.54 ± 17.88 years were evaluated (78% male). 248 (56%) patients underwent selective CT scan and 195 (44%) underwent pan CT scan. The 2 groups were similar regarding vital signs and mean age. Mean hospital length of stay was 21.05 ± 24.64 days for selective CT scan group and 18.18 ± 22.75 days for the other one (p = 0.209). A significant difference was only seen regarding findings of chest injury between the 2 groups (p < 0.001). In other cases a proper overlap was seen between findings of the 2 groups. Conclusion: Based on the results of the present study, it seems that doing selective CT scan yields results similar to pan CT in detection of head and face, neck and abdomen and hip injuries in multiple trauma patients. However, using pan CT in these patients led to 16% increase in detection and diagnosis of traumatic intra-thoracic injuries.